Wernicke encephalopathy in a patient with drug-induced liver failure: a case report - Cao, Jiao-Jiao; Li, Jing; Cheng, Yan; Luo, Li-Min; Chen, Yang; Huang, Chang-Xing; Zhang, Ye (Frontiers in Nutrition, 2025)
IntroductionWernicke encephalopathy is a metabolic disease mainly associated with vitamin B1 deficiency, which is common in chronic alcoholism. Non-alcoholic Wernicke encephalopathy is difficult for early diagnosis.Case presentationOne case involved a 62-year-old man who was admitted to hospital with drug-induced liver failure. He presented lower extremity weakness and progressive worsening of consciousness disturbance post-admission and was eventually identified as Wernicke encephalopathy by magnetic resonance imaging scan and deficiency in vitamin B1. The classic symmetric hyperintense signals on T2-weighted and diffusion-weighted images were reversible after intravenous vitamin B1 supplementation.ConclusionA high index of clinical suspicion is required for early diagnosis and appropriate preventive and therapeutic strategies by adequate and immediate vitamin B1 supplements in the reversible stage of Wernicke encephalopathy.